Change Orders and Lessons Learned: Knowledge from Statistical Analyses of Engineering Change Orders on Kentucky Highway Projects - Taylor, Timothy R. B; Uddin, Moin; Goodrum, Paul M; McCoy, Alex; Shan, Yongwei (Journal of construction engineering and management, 2012)
AbstractAlthough change orders occur on many construction projects, data examined in this paper suggest that many change orders can be avoided on roadway construction projects through improved project planning and scoping. Statistical analyses of change orders on 610 Kentucky roadway construction projects from 2005–2008 examined how the causes of change orders varied between construction versus maintenance projects, different road types (e.g., state highways, interstate, and county roads), and construction type (e.g., earth work, structures, and road surfacing). The research examined the risk posed by engineering change orders by measuring the frequency and average percentage change in project costs for different types of change orders. Although the relative impacts did vary by analyses, the leading causes of change orders within the state consistently included contract omissions, owner-induced enhancements, and contract item overrun. The paper’s primary contribution to the overall body of knowledge is the establishment of evidence that many high risk change orders on roadway construction projects can be avoided through improved front end planning, whereas avoidance of other change orders, such as fuel and asphalt price adjustments, are more challenging because they can be caused by rapidly changing market conditions. The results show not only distinctive trends that are useful for constructability reviews on future projects, but also identify the need for new directions in front end planning and project scoping to minimize change orders on highway projects.